2004
DOI: 10.1080/07399330490475575
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Functioning in Women With Fibromyalgia: A Grounded Theory Study

Abstract: The aim of this study was to elucidate psychological functioning and psychological processes in women with fibromyalgia. Twenty-one females with fibromyalgia (aged 26-72 years) were interviewed in-depth. The interviews were analysed in line with grounded theory. A core concept, "unprotected self," mirroring childhood conditions and adult psychological functioning, was identified. Intense activity or hypomanic helpfulness often was used as self-regulation in adult life. Later an increased exposure to mental loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…Notwithstanding limitations of cross sectional life stress research including the present one, this study confi rms importance of stressful life events in pathogenesis and maintenance of chronic pain. Longitudinal data considering multidimensional factors in combination with use of sophisticated interview based strategies (Wentz, Lindberg & Hallberg, 2004) may facilitate the exploration of causal relationship between stress and pain. Furthermore, the study underlines the importance of examining the occurrence of life events beyond its simple count and suggests scrutinizing the specifi city of these events.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding limitations of cross sectional life stress research including the present one, this study confi rms importance of stressful life events in pathogenesis and maintenance of chronic pain. Longitudinal data considering multidimensional factors in combination with use of sophisticated interview based strategies (Wentz, Lindberg & Hallberg, 2004) may facilitate the exploration of causal relationship between stress and pain. Furthermore, the study underlines the importance of examining the occurrence of life events beyond its simple count and suggests scrutinizing the specifi city of these events.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from performance demands, patients may find leisurely activities aversive because their thinking patterns, if not intently focused on external obligations, will naturally settle on highly negative perceptions of themselves, e.g., laziness or badness (Johnson et al, 1997;Wentz, Lindberg, & Hallberg, 2004). Thus, their dedication to almost continuous high-effort activities appears to serve in part the purpose of effectively blocking these negative self-reflections.…”
Section: Presence/absence Of Pleasant Affect and Experiences And Socimentioning
confidence: 90%
“…However, fibromyalgia researchers should be aware of recent methodologic advances in the area of life stress research, such as the use of sophisticated interview-based strategies that may reveal subtle "inner stressors" associated with personality features and life history [15], as well as "ecologic momentary assessment," "experience sampling" methods, and "multivariate time series" that allow a detailed longitudinal view on the impact of daily life stressors on symptoms [31,32].…”
Section: Assessing Life Stressmentioning
confidence: 99%
“…From a totally different perspective, Wentz et al [15] focused on fibromyalgia patients' life stress by using qualitative research strategies based on "grounded theory". The authors concluded that their fibromyalgia patients were pre-morbidly characterized by the core feature of "an unprotected self," which they overcompensated by intense activity or hypomanic helpfulness.…”
Section: Life Stress During Adulthoodmentioning
confidence: 99%